Moriarty : a novel - Horowitz, Anthony, 1955- (Harper, an imprint of HarperCollinsPublishers, 2014)
Days after the encounter at the Swiss waterfall that claimed the lives of Sherlock Holmes and criminal mastermind Professor Moriarty, Pinkerton detective agent Frederick Chase and Scotland Yard Inspector Athelney Jones, a devoted student of Holmes's methods of investigation and deduction, must track down a sinister figure who is determined to stake his claim as Moriarty's successor.